Cultural and Linguistic Insights through Green Day's Lyrics for EFL Students - Arnelli, Arnelli (Jurnal Pendidikan Bahasa, 2024)
This study explores the potential of Green Day's lyrics as an educational resource for English as a Foreign Language (EFL) learners. While traditional language instruction often lacks the cultural and emotional dimensions of authentic language, song lyrics can bridge this gap. Focusing on three Green Day songs—"American Idiot," "Boulevard of Broken Dreams," and "Wake Me Up When September Ends"—this qualitative analysis examines recurring themes, vocabulary, and sociocultural content. Findings reveal that these songs provide learners with relatable content, idiomatic expressions, and a rich array of colloquial vocabulary, supporting vocabulary acquisition and conversational fluency. Moreover, Green Day's lyrics offer insight into American society, including themes of media influence, identity, and social critique, fostering cultural awareness and critical thinking among learners. The emotional engagement provided by these themes also enhances memory retention, aligning with Krashen’s Affective Filter Hypothesis. This study suggests that popular music, particularly songs with cultural depth, can enhance EFL learning by offering an immersive, authentic experience.